Avaliação da biodisponibilidade e a bioacumulação de metais em botos-cinza do complexo estuarino-lagunar de Iguape-Cananéia, SP - Salgado, Lilian Dalago (2015)
The Ribeira de Iguape river is the most responsible for the input of freshwater and sediments in suspension to the Estuarine-Lagoon Complex of Iguape-Cananéia (CELIC), which has a population of about 200 Guiana dolphins. The basin of this river was strongly affected by mining activities, which contaminating the sediments along its course and in part of the estuary. This study evaluated the spatial and temporal variation of physical and chemical parameters of the environment, the bioavailability of Fe, Zn, Mn, Co, Cu, Cr, Cd, Pb and Ni in the sediments and the accumulation of these elements in the liver of 21 dolphins of the species Sotalia guianensis. The water and sediment were sampled in 8 points throughout the system in three different samples between the years 2013 and 2014 and the tissue samples were obtained by monitoring of the beaches between 2009 and 2012. The trophic conditions found between the portions differ in great degree, most notably salinity, resistivity,DO, pH and the supply of nutrients and metals. The metals Pb, Zn, Cu, Mg and Fe showed high values in sediments near Iguape, being considered as strong bioavailable. The SEM/SVA reason for the metalic ions Pb, Cd, Ni, Cu and Zn showed greater toxicity of the sediments in this region. There were positive correlations between these elements indicating that they probably have the same sources, from the drag made by the Ribeira river. In the liver of the dolphins, the concentrations were given in the following order of magnitude: Fe>Zn>Cu>Mn>Cr> Pb>Ni>Co>Cd. The metals Fe and Zn showed higher values between metals and the Pb had the highest mean and variance ever described for the species (1.94 μg g-1). There were no correlations in the accumulation of metals between the sexes and the body length of the animals. However, infants showed higher concentrations of essential metals, and these values are related to the periode of rapid postnatal growth. Considering the local history and the bioavailability values observed for the metals, this study emphasizes the use of the Guiana dolphin as sentinel, this being an important approach for environmental monitoring once it allows direct measurement of the bioavailability of metals. The high mean of lead observed in the dolphings may reflect the local environmental contamination caused by mining activities and indicate a possible trophic transfer, since the diet is a major route of exposure to the element.